2013
DOI: 10.1074/jbc.m112.434217
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Substrate Preference for GAB1 Protein Bestows Transforming Activity to ERBB2 Kinase Lung Cancer Mutants

Abstract: Background: Activating ERBB2 mutants drive tumor formation. Results: Oncogenic ERBB2 has a striking substrate preference for GAB1 in vitro, and GAB1 hyper-phosphorylation is required for mutant ERBB2-induced cell signaling and transformation. Conclusion: Acquired substrate preference for GAB1 is critical to the ERBB2 mutant-mediated oncogenesis. Significance: Understanding the activation mechanism of mutant ERBB2s may lead to the development of therapies targeted against these oncogenic kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Our study for the first time identified GAB1 as a target of miR‐409‐3p in CRC and revealed its unique function in CRC cell migration and invasion, suggesting an important role of abnormal GAB1 expression in CRC progression. Therefore, in addition to post‐translational regulation of GAB1 by phosphorylation, the study by Mraz et al . and our study indicate that the post‐transcriptional regulation of GAB1 expression, for example, by miRNA, might be a novel mechanism by which GAB1 regulates cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our study for the first time identified GAB1 as a target of miR‐409‐3p in CRC and revealed its unique function in CRC cell migration and invasion, suggesting an important role of abnormal GAB1 expression in CRC progression. Therefore, in addition to post‐translational regulation of GAB1 by phosphorylation, the study by Mraz et al . and our study indicate that the post‐transcriptional regulation of GAB1 expression, for example, by miRNA, might be a novel mechanism by which GAB1 regulates cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…GAB1 (Grb2‐associated binding protein‐1) belongs to a family of docking proteins (GAB1, GAB2, GAB3), that when phosphorylated are involved in mediating signal transduction of RTK pathways 28,29 . Preclinical data has shown that GAB1 expression in carcinomas is required for EGF receptor signaling through MAPK and AKT signaling and may play a role in carcinogenesis 30,31 . ABL (Abelson murine leukemia) family proteins, including ABL1 (chr 9q34) and ABL2 (chr 1q25) are proto‐oncogenes that code for ubiquitously expressed tyrosine kinases, which play an important role in cellular division, differentiation, survival/death, and migration 32 .…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Preclinical data has shown that GAB1 expression in carcinomas is required for EGF receptor signaling through MAPK and AKT signaling and may play a role in carcinogenesis. 30,31 ABL (Abelson murine leukemia) family proteins, including ABL1 (chr 9q34) and ABL2 (chr 1q25) are proto-oncogenes that code for ubiquitously expressed tyrosine kinases, which play an important role in cellular division, differentiation, survival/death, and migration. 32 Abnormal constitutive activation of ABL activity through development of fusion proteins has been shown to play a role in human cancer, including BCR-ABL, ETV6-ABL, EML1-ABL, among others.…”
Section: Casementioning
confidence: 99%
“…Briefly, keratinocytes were isolated from skin of 1- to 3-d-old mice, pooled, and maintained in Ca 2+ -free minimal essential medium supplemented with 8% chelexed fetal bovine serum, 0.05 mM Ca 2+ , and penicillin/streptomycin. The pSLIK-Neo/TRE Pitt lentiviral vector plasmids encoding V5-tagged Ras and dominant-negative (S17N) Ras and lentivirus were generated as described previously (Fan et al , 2013). Primary keratinocytes were transduced by lentivirus, and the following day, expression was induced overnight with 20 ng/ml doxycycline (cat.…”
Section: Methodsmentioning
confidence: 99%
“…GTX627408; 1:1000; GeneTex) were used for Western blotting. Western blotting was performed as previously described (Fan et al , 2013).…”
Section: Methodsmentioning
confidence: 99%